(untitled) (Fiep Bulletin - online, 2011)
This study had as an objective analyzed the psychomotor profile of subject has special needs of a school of the public education of Ipatinga, MG. It was participated of these study 10 students of both genres, in the age between 6 and 10 years old. For to evaluate the motor development was utilized the Fonseca’s psychomotor battery (1992), that is constituted of the tests: static and dynamic equilibrium, body notion, lateral notion, space/ time structuring, global and thickness praxia. With the obtained results it was verified that the students that has special needs of this school has high discrepancy in their psychomotor development, needing Will be better stimulated and rehabilitated.